Política de expansão da UERN: oferta e qualidade da educação superior - Andrade, Maria Edgleuma de (2012)
The purpose of this study was to analyze the configuration of the higher education expansion process during the period from 2002 through 2008 in the State University of Rio Grande do Norte UERN in its institutional context, in order to understand the capacity of this university for establishing the consolidation and sustainability of its expansion. This research adopted a case-study based on a qualitative approach (NÓVOA, 1991; YIN, 2005). The methodological path consisted of a bibliographic review of the relevant literature and a documentary research which was carried out through the analysis of official documents of multilateral agencies (UNESCO and World Bank); official documents concerning the national and state legislation, and institutional documents of UERN, in order to analyze the effective developments related to its expansion policy. The data were processed based on the analytical descriptive method (TRIVIÑOS, 1987) guided by the hypothesis and theoretical framework, which permitted the understanding of the general aspects of the investigated reality in line with the proposed objectives. The theoretical inputs of this study came from the concepts of sustaining change (CLARK, 2004), combined with the emancipatory logic (SANTOS, 1995; 2006), and were articulated to the debate around the analysis categories: democratization (DIAS SOBRINHO, 2005; 2010; CHAUÍ, 2003; RISTOF, 2008); autonomy (FÁVERO, 2004; DURHAM, 2003; RANIERI, 2005; CUNHA, 2006) and quality (UNESCO, 1998; DIAS SOBRINHO, 2005a; 2008; 2010; MOROSINI, 2001; 2009). The study results showed that UERN's expansion policy converges towards a partial sustainability as it potentiates medium and long term actions that allow this institution to fulfill its role as a university. Contradictions and limitations occurred, however they did not hamper progress, being also transformation elements to the expansion policy. The university showed positive indicators, which were permeated with some limitations: a) democratization: noticeable is the expansion of educational opportunities which occurred through the increase of access, staying policies, expansion of investments, and open public selections of teachers ; b) quality: the strengths related to this dimension are the actions aimed to strengthen the research activities in the institution, and the investments in the Teachers Training Program; c) autonomy: regarding the didactical-academic autonomy, noticeable was the academic freedom of the university in its decision processes concerning to teaching, research and extension; However, the major limitation is the absence of administrative and financial autonomy in the Advanced Centers of Higher Education of this institution, whose fragility is evidenced. Given the analysis benefits, this study demonstrated that the UERN s expansion policy has occurred with actions and decision processes of partial sustainability, constituting a result of the dialectical expression of its singularities, specificities, and contradictions which also are transformation factors; and allowed progresses and limitations in some moments of its expansion.